Spatial Distribution Characteristics and the Evolution of Buddhist Monasteries in Xi’an City Area - Song, Hui (Religions, 2023)
Buddhist monasteries have played important roles in the development of both the culture of and urban planning in ancient Chinese cities. In this paper, the Buddhist monasteries in the city of Xi’an, Shaanxi Province, during the Song (宋), Yuan (元), Ming (明), and Qing (清) dynasties are collated from historical documents. The characteristics of the spatial distribution of Buddhist monasteries are analyzed by using kernel density estimation (KDE), and the evolution of that spatial distribution is explored by documentary analysis. The results show that Buddhist monasteries are closely surrounded by cultural buildings and warehouses, discretely surrounded by administrative buildings. The spatial distribution evolution of Buddhist monasteries has evolved evenly during the expansion of the Xi’an city area, through the Song, Yuan, Ming, and Qing dynasties. This study provides a reference for the preservation of Buddhist monastery spaces in the historical context of Xi’an city area.